(untitled) (MAUSAM, 1987)
The probability estimates of historical weekly rainfall (R) and potential evapotranspiration (PET) records appeared to be a quite useful tool for studying the continuity of rainfall receipts. In the district of Nadia in West Bengal, the probability, of continuance of rain is fairly dependable, after 19th week (7 to 13 May) and rainfed crops sown after this period will escape maximum risks of water deficits occurring in the early stage of crop growth before the onset of monsoon. When available-water storage is considered with rainfall through water balance approach the crop growth periods in different soils are augmented considerably, lying in the range of May (19th week) to February (7th week). The longest water availability duration was recorded in clay soil with 300 mm AWC, followed by in loam (250 mm A WC) and in sandy loam (200 mm AWC). Water availability periods thus computed for different soils were compared with water requirement of transplanted rice, evapotranspirations of jute and upland direct seeded rice and PET at 100 and 33% levels. Water availability periods for jute and rice-based cropping system, have thus been identified, for soils of different AWCs under rainfed condition.